2011
DOI: 10.1103/physreva.83.065401
|View full text |Cite
|
Sign up to set email alerts
|

Polarization limits in K-Rb spin-exchange mixtures

Abstract: We present measurements of the optical absorption of K vapor at 795 nm due to the presence of high-pressure He gas. The results set a limit on the polarization attainable in hybrid spin-exchange optical pumping of 3 He.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…where we've assumed pumping with perfectly monochromatic light with frequency ν. Measurements by Romalis et al [20] and more recently by Lancor et al [31][32][33] indicate that |T d | is of order 0.1 ps for alkali-3 He collisions. Using this value, we find that (3σ 3 .…”
Section: The Alkali X-factorsmentioning
confidence: 99%
“…where we've assumed pumping with perfectly monochromatic light with frequency ν. Measurements by Romalis et al [20] and more recently by Lancor et al [31][32][33] indicate that |T d | is of order 0.1 ps for alkali-3 He collisions. Using this value, we find that (3σ 3 .…”
Section: The Alkali X-factorsmentioning
confidence: 99%
“…At other regimes, SE collisions can be utilized to incoherently transfer polarization between different atomic states [10,11], as is widely used in the production of hyper-polarized noble gases for medical imaging [12], spin-polarized targets [13], and precision measurements [14,15]. The incoherent transfer of polarization via SE collisions was also demonstrated in a hybrid system of two alkali species [16,17], improving magnetometery sensitivity by optically pumping one specie at a given optical-depth and monitoring the other [18]. However, the coherent effects of the SE collisional interaction between different species of alkali atoms have never been investigated.In this Letter, we demonstrate a coherent coupling of two alkali species, potassium (K) and rubidium (Rb), induced by random SE collisions.…”
mentioning
confidence: 99%
“…10). This comes from off-resonant pumping of the K atoms by the resonant Rb light (Lancor and Walker, 2011) and limits the useful density ratios to 𝒟 < 10. Chen et al (2007b) observed similar results and found that the polarization decline was not observed if hybrid cells were optically pumped with 770 nm light.…”
Section: Spin-exchange Optical Pumpingmentioning
confidence: 99%
“…Finally, even for narrow band pumping hybrid K:Rb mixtures exhibit reduced maximum polarizations at high 𝒟 due to off-resonant absorption of the Rb pumping light by the K atoms (Lancor and Walker, 2011), see Fig 10. This effect limits the useful values of 𝒟 <10.…”
Section: Spin-exchange Optical Pumpingmentioning
confidence: 99%
See 1 more Smart Citation